Examination of soil agronomical structure in field experiments - Földesi, Petra; Gyuricza, Csaba (JOURNAL OF LANDSCAPE ECOLOGY, 2011)
Due to the ever increasing strive for higher yields and more intensive crop production, the tillage operations, respecting the soil fertility, the structure and the biological condition, have been pushed into the background over the past few decades. Nowadays the sustainable application of land use systems has come to the foreground, since along with the environmental polluting chemicals that are applied during the agricultural production, the improperly chosen tillage systems may cause extra expenses, soil degradation furthermore environmental damage. During our field experiments the agronomic structure of the soil, its resistance and humidity were assessed, in order to improve the physical condition of the soil. The aim of this study is to detail how the proportions of the clod, aggregate and dust fractions changed at conventional tillage under farmland conditions. In year 2004 particles of the aggregate fraction amounted to 62.8–84.0% of the soil. The clod fraction achieved 14.5–35.0%, while 1.5– 6.1% dust fractions were recorded in the examined farms. In year 2004 significant differences were recorded for the agronomic structure of the soil between the six set experiments for the clod and aggregate fractions (SD5%clod=10.2; SD5%aggregate=10.8). No significant difference could be detected between the dust fractions. Out of the 3 examined years, 2005 proved to be the one with the most precipitation, the proportion of the aggregate fraction varied between 78.6–81.8%, the clod fraction fluctuated between 15.7–19.6%, while a range of 1.5–3% was recorded for the dust fraction. In the third examined year, the proportion of the aggregate fraction was 71.4–81.5%, that of the clod fraction amounted to 17.3–26.8%, while the dust fraction represented 1.3–2% in the field experiments. When evaluating the effects of the conventional tillage system for years 2005 and 2006, no significant difference could be observed between the clod-, aggregate- and dust fraction experiments.